Real-time capable nonlinear distributed parameter observer considering two-phase flow in PEM fuel cells - Kravos, Andraž; Vrlić, Martin; Hametner, Christoph; Jakubek, Stefan; Katrašnik, Tomaž (International journal of hydrogen energy, 2025)
This paper presents a breakthrough in real-time capable nonlinear distributed parameter observation of spatially resolved intra-PEMFC states, which is achieved by developing an innovative PEMFC observer framework based on the Unscented Kalman Filter, novel method for determining physically motivated constraints for corrective actions, and real-time capable state-of-the-art spatially resolved physio-chemically consistent distributed parameter model considering two-phase flow. The proposed framework enables unprecedented real-time insight into the spatially distributed dynamics of water in liquid and gaseous states, as well as phase transformation, membrane water uptake, and into the impact of gas crossover effects on the mixed potential of PEMFCs just from lumped voltage, serving as an output, and current trace serving as an input. These advanced functionalities were formally confirmed by observability and comparative analysis using experimental results obtained from a segmented PEMFC and achieving very high R2 values between 0.9976 to 0.9987, hence, confirming computationally-efficient beyond state-of-the-art control functionality. •Real-time capable nonlinear distributed parameter observer is developed.•Observes water dynamics, phase changes, and gas crossover effects.•Uses Unscented Kalman Filter with novel, physically motivated constraints.•All states are formally observable from lumped voltage and current trace only.•Enables advanced, cost-effective control for enhanced PEMFC performance and longevity.